Handbook of marketing decision models - Wierenga, B.; Van der Lans, Ralf (Springer, 2017)
"The Second Edition of this book presents the state of the art in this important field. Marketing decision models constitute a core component of the marketing discipline and the area is changing rapidly, not only due to fundamental advances in methodology and model building, but also because of the recent developments in information technology, the Internet and social media. This Handbook contains eighteen chapters that cover the most recent developments of marketing decision models in different domains of marketing. Compared to the previous edition, thirteen chapters are entirely new, while the remaining chapters represent complete updates and extensions of the previous edition. This new edition of the Handbook has chapters on models for substantive marketing problems, such as customer relationship management, customer loyalty management, website design, Internet advertising, social media, and social networks. In addition, it contains chapters on recent methodological developments that are gaining popularity in the area of marketing decision models, such as structural modeling, learning dynamics, choice modeling, eye-tracking and measurement. The introductory chapter discusses the main developments of the last decade and discusses perspectives for future developments"--Provided by publisher.
Keywords: Marketing -- Decision making -- Mathematical models.; elektronické knihy; electronic books